Cambio climático, recursos naturales y conflicto - Carius, Alexander; Maas, Achim (Revista Española de Desarrollo y Cooperación, 2023)
This article will provide an overview to the ongoing scientific and political debate on interlinkages between climate change and conflict. First, it will outline the key challenges of climate change. Second, the main relationships between climate change and conflict will be scrutinized. This will include an overview, how responses to climate change such as mitigation and adaptation measures could also become security risks. Finally, the emerging political processes to tackle the security challenges of climate change will be discussed.